2021
DOI: 10.1016/j.jbc.2021.100698
|View full text |Cite
|
Sign up to set email alerts
|

Lectins engineered to favor a glycan-binding conformation have enhanced antiviral activity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It is worth noting that the study of Matoba et al [19] increased the antiviral activity of lectins. Such proteins have as characteristics the recognition and maintenance of specific and reversible bonds to mono-or oligosaccharides and other substances containing sugars, maintaining the covalent structure of these glycosidic ligands [19]. They can precipitate cells, glycoconjugates, and polysaccharides from animal, plant, virus, and bacterial sources [20,21].…”
Section: Lectin Activitymentioning
confidence: 94%
“…It is worth noting that the study of Matoba et al [19] increased the antiviral activity of lectins. Such proteins have as characteristics the recognition and maintenance of specific and reversible bonds to mono-or oligosaccharides and other substances containing sugars, maintaining the covalent structure of these glycosidic ligands [19]. They can precipitate cells, glycoconjugates, and polysaccharides from animal, plant, virus, and bacterial sources [20,21].…”
Section: Lectin Activitymentioning
confidence: 94%
“…For example, the engineered Pseudomonas taiwanensis lectin (PTL) bind high-mannose glycans on the HA protein of the influenza virus, thereby inhibiting the entry of viral particles. 13 BanLec (an engineered plant lectin isolated from the fruit of bananas) is another recombinant lectin with anti-viral activity against HIV, HCV, and influenza virus, all of which have high-mannose-type N-glycans on their surfaces. Because BanLec exhibited a strong T-cell mitogenic response, a recombinant H84T mutant was generated to reduce mitogenicity while preserving the virucidal activity.…”
Section: Recombinant Lectins As Anti-viral Agentsmentioning
confidence: 99%
“…Lectin-induced mitogenicity can be overcome by attempting glycoengineering techniques such as BanLac, which was engineered to eliminate its mitogenicity by amino acid mutation at position 83–84 from histidine to threonine [19] , without compromising antiviral activity against Ebola and influenza viruses [20] , [21] . In another recent study published in April 2021, a site-specific engineered lectin based on structural insights, Pseudomonas taiwanensis lectin (PTL), reportedly enhanced antiviral activity against the influenza virus and such site-specific engineering of lectins can be a potential strategy to boost the antiviral activity of lectins [22] . The data from 2015 to 2020 showed that numerous potential antiviral lectins were discovered along with studies of structural modifications when needed [23] .…”
Section: Introductionmentioning
confidence: 99%